The effect of elderly gymnastics on mean arterial pressure (MAP) in elderly with hypertension in Gayam Hamlet, Prambanan District, Sleman Regency - Sinandang, Agnes Ayuarista Adyastuti; Marlina, Theresia Titin; Wulandari, Riski (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Hypertension is a disease characterized by increased blood pressure. This disease is common in the elderly due to decreased physical strength and function as they age. Basic health research in 2018 found that hypertension is the number one cause of death in Indonesia. Yogyakarta has a prevalence of 32.86% while the >65-year-old age group dominates at 64.78%. Data from the Public Health Office for the district with the highest incidence of hypertension is Sleman, with a total of 138,702 cases. Therefore, prevention and ways to control hypertension in the elderly need to be done, one of which is by changing behavior to be healthier such as simple sports activities such as elderly gymnastics. Elderly gymnastics can help widen blood vessels to maintain blood pressure stability.Methods: The research method used a quantitative pre-experimental design with a one-group pretest-posttest design approach. Measurement of mean arterial pressure (MAP) was carried out before elderly gymnastics on the first day of gymnastics and measured again on the last day after gymnastics was completed. The sample used was total sampling, total 36 patients who met the inclusion criteria. Statistical tests used the Wilcoxon test because the data distribution was not normal.Results: The results showed that the average Mean Arterial Pressure (MAP) score before elderly gymnastics was 116.15 mmHg and after elderly gymnastics was found to decrease to 104.68 mmHg. Based on the results of the Wilcoxon test, the p-value is 0.000 (<0.05).Conclusions: There is a significant effect of elderly gymnastics on the mean arterial pressure (MAP) of elderly people with hypertension in Gayam Hamlet, Prambanan District, Sleman Regency.